Long-term effects of an intensive voice treatment for vocal fold nodules. (2nd January 2016) - Fu, Sherry; Theodoros, Deborah; Ward, Elizabeth C.
Abstract: Purpose : The purpose of the current study was to examine the long-term effects of intensive voice treatment for vocal fold nodules, compared to outcomes for patients treated with traditional voice therapy. It was hypothesised that intensive treatment would provide comparable maintenance of vocal function, voice quality, and patients' perception of quality-of-life when compared with traditional treatment at 6 month follow-up. Method : Thirty-six women diagnosed with bilateral vocal fold nodules who were treated with either traditional ( n = 20; once a week for 8 weeks) or intensive ( n = 16; eight sessions within 3 weeks) therapy. Each participant completed voice, stroboscopic, and acoustic assessments and the Voice Handicap Index before, immediately post and 6 months post-treatment. Result : Results revealed most improved perceptual, stroboscopic and acoustic parameters were maintained in both groups at 6 months post-treatment, with no significant differences between the two groups. In addition, both groups maintained satisfaction on their perception of vocal function, with no significant difference between the two groups. Conclusion : The investigation provided further evidence that individuals with vocal fold nodules are able to maintain improved voice quality and vocal health following intensive voice treatment to a similar degree to traditional voice treatment.